ESR investigation of hydrogen and deuterium atoms in impurity-helium solids - Kiselev, S.I.; Khmelenko, V.V.; Bernard, E.P.; Lee, D.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Impurity-helium solids (Im-He solids) are porous solids created by injecting a beam of mixed helium and impurity gases into superfluid 4He. In this work we use electron spin resonance (ESR) techniques to investigate Im-He solids containing atoms and molecules of hydrogen and/or deuterium. We have performed studies of low temperature (T 1.35 K) tunnelling chemical reactions in which deuterium atoms replace the hydrogen atoms bound in H2 or HD molecules to produce large (up to 7.5×1017cm-3) and relatively stable concentrations of free hydrogen atoms. The time dependence of H and D atom concentrations has been investigated for Im-He samples with different initial ratios of hydrogen and deuterium ranging from 1:20 to 1:1.The satellite ESR lines associated with the dipolar coupling of electron spins of H and D atoms to the nuclear moments of the hydrogen nuclei found in neighboring molecules have been observed in Im-He solids. The forbidden hyperfine transition of atomic hydrogen involving the mutual spin flips of electrons and protons has also been observed.